Aurora kinases as targets for cancer therapy - Mountzios, G.; Terpos, E.; Dimopoulos, M.-A. (Cancer Treatment Reviews, 2008)
Aurora kinases represent a family of serine/threonine kinases highly conserved during evolution, whose main function is to promote mitotic spindle assembly by regulating centrosome duplication and separation. Inhibition of Aurora kinase activity may lead to defects in centrosome function, misaligned sister chromatides, mitotic spindle malformation, problematic cytokinesis and eventually mitotic arrest. Aurora kinases are overexpressed in a variety of tumor cell lines, suggesting their potential role in tumorigenesis and indicating that they could represent an appealing target for molecular therapies. Extensive pre-clinical information supports the development of Aurora kinase inhibitors in specific tumor types and a number of these novel agents are currently being extensively studied in phase I and II clinical trials exhibiting an acceptable toxicity profile and promising clinical efficacy. The current study aims to provide a comprehensive overview of the development of Aurora kinases as molecular targets for anticancer therapy by focusing on their physiological role in mitosis, their implication in oncogenesis and the potential ways of inhibiting their activity. The main pre-clinical and clinical studies concerning Aurora kinase inhibitors currently under investigation are reported and important considerations for their future development are discussed. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Aurora A; Aurora B; Aurora C; Aurora kinase inhibitors; Aurora kinases; Mitosis